Plasma Beta-Trace Protein as a Marker of Residual Renal Function: The Effect of Different Hemodialysis Modalities and Intra-Individual Variability over Time - Amaryllis H. van Craenenbroeck; Ann-Christin Br; Abdul Rashid Qureshi; Bengt Lindholm; Bodil Sjöberg; Björn Anderstam; Olof Heimburger; Peter Stenvinkel; Peter Bárány (Karger Publishers, 2017)
Background/Aims: Beta-trace protein (BTP) is a low-molecular-weight molecule, which may be used to assess residual renal function (RRF) in dialysis patients. Here we evaluated the influence of hemodialysis (HD) and hemodiafiltration (HDF) on plasma BTP, and analyzed the inter- and intra-individual variability of plasma BTP over time in HD and peritoneal dialysis (PD) patients. Methods: In 12 prevalent HD patients, the effect of a single session of low-flux HD, high-flux HD and HDF on plasma BTP was studied. Blood samples were taken at baseline, after 120 and 240 minutes, and at the start of the next dialysis session. In 13 HD patients and 10 PD patients, inter- and intra-individual variability over three months was studied (monthly and weekly, respectively). Plasma BTP was measured using a nephelometric method. Results: No significant decrease in plasma BTP was seen following a session of low-flux HD. Both high-flux HD and HDF resulted in a significant decrease immediately after dialysis (22% and 61% median decrease, respectively). A significant reduction of the molecule persisted only in HDF and a significant decrease (-15%) was still found immediately before the start of the next dialysis session. In both HD and PD patients, the reproducibility over time was excellent with intra-class correlation coefficient of 0.96 (0.93-0.99) and 0.92 (0.86-0.99) respectively. In a small cohort of PD patients, fair agreement existed between mGFR (average of renal urea and creatinine clearance from a 24 hours urine collection) and the BTP-based GFR estimation. Conclusion: BTP is a stable marker and a promising tool for RRF estimations in PD and HD patients. In patients receiving HDF, plasma levels of BTP should be interpreted with caution.